THE CORRELATION BETWEEN STUDENTS’ READING ATTITUDE AND THEIR READING ACHIEVEMENT OF EIGHTH GRADE IN ENGLISH CLASSES AT SMPN 7 KOTABUMI ACADEMIC YEAR 2022/2023 - Sindi Dwi Aprilia; Dewi Sri Kuning; Dewi Sartipa; Melly Andini; Lily Ivana; Tangkas Auliaartha Mukti; Marshanda Ordena; Ria Mei Yustisia (Universitas Muhammadiyah Kotabumi, 2023)
Reading attitude is a person's attitude towards reading, a mental condition accompanied by sentiments and emotions that influence how much a person tends to read. Researcher show that attitudes have a correlation with students' reading achievement but technical researcher conducted observations in the eighth grade of SMPN 7 Kotabumi, researcher found that student problems existed; Reading practice makes students bored, students have difficulty interpreting the implied meaning in the text, and some students have little desire to read. The purpose of this research is to find out whether there is a correlation between students' reading attitudes and students' reading achievement in English. The research method is a quantitative method. The population in this study were all class VIII students at SMPN 7 Kotabumi for the 2022/2023 academic year, consisting of 261 class VIII students, so in sampling the researcher used cluster random sampling in class VIII F of 32 students. The instruments used are questionnaires and documentation. Try out were also carried out at SMPN 1 Kotabumi for the 2022/2023 academic year in class VIII A for 32 students. The average reading achievement statistical result is 74.50. The normality test results for reading attitudes were 0.158 and reading achievement were 0.719 > (0.05), so it can be concluded that the data was normally distributed. The Homogeneity test results are 0.957 > (0.05) so it can be concluded that the variables of reading attitude and reading achievement have a linear correlation. So the hypothesis test is 0.127>(0.05)= 0.127 and the variable Reading Attitude and Reading Achievement has a positive correlation, meaning that if Reading Attitude increases, Reading Achievement will also increase.